PENGARUH LOCUS OF CONTROL, FINANCIAL SOCIALIATION DAN PARENTAL NORMS TERHADAP FINANCIAL MANAGEMENT BEHAVIOR DENGAN FINANCIAL LITERACY SEBAGAI VARIABEL INTERVENING PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI MAKASSAR - Neneng Hidayat; Ali Muhson; Muh. Firdaus (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to determine the influence of Locus of Control, Financial Socialization, and Parental Norms on Financial Management Behavior with Financial Literacy as an Intervening Variable among Economics Education Students at Makassar State University. This research is quantitative, with a total population of 640 students from the Faculty of Economics as recipients of the Bidikmisi Scholarship Program. A sample was then obtained based on the Slovin formula of 246 students. The results of this research are: (1) Locus of control has no effect on financial management behavior; (2) Financial Socialization has an effect on financial Management Behavior, (3) Parental Norms have an effect on financial management behavior; (4) financial literacy has no effect on financial management behavior; (5) Locus of Control has an effect on financial literacy; (6) Financial Socialization has no effect on financial literacy, (7) Parental norms have no effect on financial literacy; (8) Locus of Control has no effect on Financial Management Behavior through financial literacy; (9) Financial Socialization has no effect on financial management behavior through financial literacy; (10) Parental Norms have no effect on financial Management Behavior through Financial Literacy among Makassar State University students in the class of 2020.